2006
DOI: 10.1111/j.1365-2028.2006.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between large African browsers and thorny Acacia on a wildlife ranch in Kenya

Abstract: Some plants respond to browsing with compensatory regrowth of plant tissues and with increased thorn growth. Associations between browsers and their preferred forage were examined through wandering quarter vegetation sampling and observational studies in an effort to understand how some plants respond to browsing by large African herbivores. Acacia seyal (n ¼ 2680) A. drepanolobium (n ¼ 1850), and Balanites glabra (n ¼ 960) were three species of frequently browsed indigenous plants examined on Game Ranching Lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…For example, induction of trichomes in B. nigra varied significantly in magnitude and timing in response to three different insect species (Traw & Dawson 2002). Additional studies in the field measuring induction by naturally occurring herbivory undoubtedly include responses to multiple species (Rohner & Ward 1997;Milewski & Madden 2006;Mizumachi et al 2012;Frederickson et al 2013), but without controlling herbivore identities, it is impossible to assess specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, induction of trichomes in B. nigra varied significantly in magnitude and timing in response to three different insect species (Traw & Dawson 2002). Additional studies in the field measuring induction by naturally occurring herbivory undoubtedly include responses to multiple species (Rohner & Ward 1997;Milewski & Madden 2006;Mizumachi et al 2012;Frederickson et al 2013), but without controlling herbivore identities, it is impossible to assess specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the mechanisms underlying induction is particularly needed for woody plants in tropical regions. Much of the early pioneering work, as well as recent work, on the induction of spinescence has been done on African Acacia trees (many of which have now been reorganized into different genera), and these studies have shown that trees exposed to browsing by large mammals, including gazelles, elephants and giraffes, tend to have larger and greater densities of spines, thorns and prickles, than plants protected from browsers (Young 1987;Milewski, Young & Madden 1991; Log odds ratio Gowda 1997;Young & Okello 1998;Gadd, Young & Palmer 2001;Young, Stanton & Christian 2003;Scogings & Macanda 2005;Milewski & Madden 2006). In many of these studies, induction is actually inferred from the relaxation of spinescence following herbivore exclusion treatments in which densities or sizes of thorns and spines decrease following herbivore removal (Young & Okello 1998;Zinn, Ward & Kirkman 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Responses of spines have been mainly studied in Acacia species, showing increased spinescence (e.g. Fornara and du Toit 2007;Goheen et al 2007;Zinn et al 2007), but thorns of Balanites glabra are green, modified shoots, which became shorter under severe browsing because browsing induces early maturation (Milewski and Madden 2006). Spinescence has not been studied in relation to browsing intensity is an example of the type of functional framework that can be used for further research.…”
Section: Browsing Intensity-carbon Limitation Thresholdsmentioning
confidence: 99%
“…Early research teams could only speculate about how plants responded to browsers; however, over time each team became part of an ongoing project that clipped thorns from acacia trees and conducted other experimental activities that made it possible to gage plants' specific growth in response to browsing pressure. Students provided new information about how plants fight back against large browsing mammals in African Savannas (Milewski & Madden, 2006). This success was largely a result of long-term, ongoing studies that were gradually improved by different teams of students working over several months.…”
Section: Discussionmentioning
confidence: 98%